Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

prove

Asked by 30th July 2012, 3:41 PM
Answered by Expert
Answer:
(1/sin10) - (sq.root3/cos10)= {cos10 - ? 3 sin10}/sin10 cos10
= 2 { cos10 - ? 3/2 sin10}/sin10 cos10
=2(cos60cos 10- sin60sin10)/{2sin10 cos10} 
Since =cos60 and ? 3/2=sin60
2cos(60+10)/{sin20}=4cos70/sin20 
= 4cos70/sin(90-70) since sin20=sin(90-70)= cos70
=4cos70/cos70= 4
Answered by Expert 30th July 2012, 4:20 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp